Dielectric properties of La0.67sr0.33Mnl-xTix03 with x = 0.4 and 0.6. - Zalita , Z.; Shaari, Abdul Halim; Wan Yusoff, Wan Mohamad Daud; Lim, Kean Pah; Talib , Zainal Abidin; Mazni, M. (Malaysian Solid State Science and Technology Society (MASS), 2011)

(untitled)
The dielectric properties of Ti-substituted La0.67Sr0.33Mn1-xTixO3 with x = 0.4 and 0.6 as a function of frequency and temperature have been investigated. The samples have been prepared using the conventional solid state reaction method at 1300oC. Both samples showed rhombohedral structure with R3C space group. The grain size of x = 0.4 and 0.6 are ~2.5 to 3.3 μm and ~0.4 to 0.9 μm respectively. The dielectric constant, ε' of the samples decreases with frequency but increases with temperature. We have successfully obtained very high dielectric constant material. The highest ε' value for LSMT with x = 0.4 and 0.6 are at frequency of 10 Hz and temperature 300 K, which are ~5.7 x 106 and ~2.4 x 106. The tan δ increases with temperature for x = 0.6 but shows a peak at a certain temperature for x = 0.4. Sample with x = 0.4 has better dielectric properties compared to x = 0.6 sample because it has higher ε' and lower tan δ value. At 175 K and 1 kHz sample with x = 0.4 shows the best dielectric properties with a high ε’ value and low tan δ which are 1.1 x 105 and 0.8 respectively.